2023
DOI: 10.1186/s12912-023-01285-x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural competence in critical care nurses and its relationships with empathy, job conflict, and work engagement: a cross-sectional descriptive study

Abstract: Background Cultural competence is more important than ever for nurses today; therefore, it may be helpful to learn more about it and examine how it relates to empathy, job conflict, and work engagement. The purpose of this study was to determine (a) the level of cultural competence, empathy, job conflict, and work engagement; (b) the relationship between cultural competence, demographic information, and main variables; (c) the predictors of cultural competence among critical care nurses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
9
0
2
Order By: Relevance
“…Factors such as excessive working hours, high workload, lack of practical experience, and frequent confrontations with fatal cases can impact the engagement of nurses in intensive care with cultural competence. Reducing the workload, providing specialised training, and regularly rotating healthcare personnel among hospital departments are essential strategies for improving cultural competence (Soleimani and Yarahmadi, 2023). The results of this study indicate that Slovak nurses with higher education perceive cultural challenges more significantly than nurses with lower education degrees (p < 0.000).…”
Section: Discussionmentioning
confidence: 77%
“…Factors such as excessive working hours, high workload, lack of practical experience, and frequent confrontations with fatal cases can impact the engagement of nurses in intensive care with cultural competence. Reducing the workload, providing specialised training, and regularly rotating healthcare personnel among hospital departments are essential strategies for improving cultural competence (Soleimani and Yarahmadi, 2023). The results of this study indicate that Slovak nurses with higher education perceive cultural challenges more significantly than nurses with lower education degrees (p < 0.000).…”
Section: Discussionmentioning
confidence: 77%
“…In particular, the "empathic feeling and expression" and "empathic perspective" were significantly more salient factors than the other two domains of ethnocultural empathy for NICU nurses. Ethnocultural empathy is a fundamental element of CC (Wang et al, 2003); previous studies have consistently reported that nurses or nursing students with a higher level of empathy had higher CC levels (Soleimani & Yarahmadi, 2023;Suk et al, 2018). A study by Hogan et al (2018) revealed increased cultural empathy among midwifery students in Australia after participating in a training program on cultural empathy, maintaining these levels a month after the program.…”
Section: Discussionmentioning
confidence: 99%
“…This study considered the concept of "ethnocultural empathy," which refers to empathy for groups of different cultures and races, as an individual factor (Wang et al, 2003). A significant positive relationship between empathy and CC among critical care nurses has been reported (Soleimani & Yarahmadi, 2023); moreover, the higher the cultural empathy level of nursing students, the higher their CC (Park & Kim, 2017). Personal experiences, including foreign language classes (Chae et al, 2012), multicultural education (Byun & Park, 2020), and cultural diversity training (Osmancevic et al, 2023), have also been shown to be associated with CC.…”
mentioning
confidence: 99%
“…It involves integrating conscious reflection and critically restructuring acquired knowledge and experiences (James et al, 2021). It is essential for nursing personnel to gain knowledge about aging and geriatric care, nurses who lack sufficient theoretical understanding and practical experience in this area may be hesitant to care for older adults after graduation (Söylemez et al, 2018;Baysal & Yildiz 2021;Soleimani & Yarahmadi, 2023).Thus, familiarity with aging, effective communication skills with older individuals, and maintaining high professional values promote positive attitudes towards working in geriatric care (Venables et al, 2023).…”
Section: Introductionmentioning
confidence: 99%